(untitled) (Журнал «Маркетинг», 2024)
This article examines the transformative evolution of global e-commerce, driven by technological advancements and shifting consumer behaviors. It emphasizes the critical role of sophisticated digital platforms in reshaping online commerce, highlighting key trends and features that facilitate these changes. The study also explores the impact of e-commerce on global marketing strategies and traces significant milestones in online shopping, underscoring the competitive dynamics between digital platforms and traditional businesses.